Exploring the spatial coupling relationship between green vegetation carbon stock and recreational intensity in urban parks: A case study of Hangzhou - Qingqing Huang; Anhua Qin; Alin Lin; Zongjie Liu (PLoS ONE, 2026)
As an important form of green space within densely built urban environments, optimizing the layout of city parks based on the synergistic integration of carbon stock and recreational services level holds significant importance. Taking Hangzhou Jinsha Lake Park as a case, this research employs remote sensing inversion to analyze the spatial distribution of the park’s carbon stock. A set of indexes was used to evaluate the park’s recreational services level. Finally, a coupling coordination model was applied to generate and visualize the coupling coordination degree between the park’s carbon stock and recreational services level. Results indicate that the coupling coordination degree between recreational services level and carbon stock in Jinsha Lake Park exhibits a distribution pattern characterized by higher values in the west and lower values in the east, as well as higher values in the south and lower values in the north. Most of these coupling coordination degrees fall in the “primary coordination” range and exhibit different spatial characteristics, such as “high recreational level – low carbon stock” and “low recreational level – high carbon stock”. Park road accessibility serves as a fundamental prerequisite for activating spaces. The rational allocation of functional zones provides a structural framework for balancing ecological and recreational interests, while optimized vegetation configuration acts as the core engine that directly drives the simultaneous growth of carbon stock and recreational vitality. Appropriate plant configuration not only directly increases regional carbon stock but also boosts recreational vitality by increasing plant diversity and vegetation coverage. This study proposes a park optimization strategy based on the synergy between carbon stock and recreational functions, which is of great significance for advancing the dual objectives of enhancing ecological services and social services in urban parks.